Pathways toward qualitative research: The lived experience of counseling psychology graduates - Srichannil, Chomphunut (Humanities, Arts and Social Sciences Studies, 2022)
Qualitative research has currently become prominent in various fields, including that of counseling psychology. In recent years, qualitative research training has been offered in some counseling psychology graduate programs in Thailand and some existing studies have suggested that there is a link between qualitative research training offered and the number of qualitative research theses conducted. However, there is a paucity of research that specifically investigates counseling psychology graduates’ motivations of undertaking qualitative research, as such, it is not yet clear what actually influences the choice of undertaking a qualitative research thesis. Thus, one of the aim of this study was to address such knowledge gap. Five graduates of counseling psychology who completed a qualitative research thesis took part in semi-structured interviews and the interview transcripts were analysed using interpretative phenomenological analysis (IPA). Two superordinate themes in relation to motivations of undertaking qualitative research were identified. The first superordinate theme, ‘The influence of past research training environment’, demonstrated how participants’ previous research training background played a significant part in shaping their prior attitudes toward qualitative research. The second superordinate theme, ‘The significant role of qualitative research training’, detailed how qualitative research training served as a catalyst for the route toward qualitative thesis research. The results highlighted the need for qualitative research training to be a core element in research training in counseling psychology, not only for enhancing students’ interest and competence in qualitative research, but also for promoting methodological diversity and advancing psychological knowledge.